Arctic Tundra Habitat Emergency Conservation Act : report (to accompany H.R. 2454) (including cost estimate of the Congressional Budget Office). - United States. Congress. Senate. Committee on Environment and Public Works. ([Washington, D.C. : U.S. G.P.O., 1999)
"October 14, 1999." Shipping list no.: 2000-0041-P. Distributed to some depository libraries in microfiche. Caption title. Mode of access: Internet.